THE ROLE OF OXIDATIVE STRESS IN THE DEVELOPMENT OF OBESITY AND OBESITY-RELATED METABOLIC DISORDERS - Čolak, Emina; Pap, Dragana (Journal of Medical Biochemistry, 2020)
Obesity is a serious medical contition, defined as excessive accumulation of fat. Abdominal fat is recognized as the major risk for obesity related diseases such as: hypertension, dyslipidemia, type 2 diabetes mellitus, coronary heart disease, stroke, non-alcoholic fatty liver disease etc. Fat accumulation is also related to pro-oxidant and pro-inflammatory states. Recently published articles suggest that oxidative stress may be a link between obesity and related complications. Adiposity leads to increased oxidative stress via several multiple biochemical processes such as superoxide generation through the action of NADPH oxidase, glyceraldehyde auto-oxidation, oxidative phosphorylation, protein kinase C (PKC) activation, and polyol and hexosamine pathways. On the other hand, oxidative stress plays a causative role in the development of obesity, by stimulating the deposition of adipose tissue, including preadipocyte proliferation, adipocyte differentiation and growth. Exercise-induced weight loss can improve the redox state by modulating both oxidative stress and antioxidant promoters, which reduce endothelial dysfunction and inflammation.